The Role of Digital Fluorescence in Acne Vulgaris: Correlation of Ultraviolet Red Fluorescence with the Severity of Acne Vulgaris - Imam Budi Putra; Nelva K. Jusuf; Nani Kumala Dewi (Dermatology Research and Practice)
Background. Colonization of Propionibacterium acnes (P. acnes) and increased sebum production play important roles in the pathogenesis of acne vulgaris. Severity of acne vulgaris correlates with the lesion counts both noninflammatory and inflammatory. Digital fluorescence has been found useful in pathogenesis investigation and treatment evaluation. Ultraviolet-induced red fluorescence (UVRF) was found to be correlated with sebum and porphyrin production that can be synthesized by P. acnes. Therefore, UVRF assessment could be useful for the evaluation of the degree and extent of acne vulgaris. Objective. To evaluate the correlation of UVRF with the severity of acne vulgaris using the digital fluorescence tool. Methods. Forty-five patients were diagnosed with mild-to-severe acne vulgaris according to Lehmann classification. Lesion counts both noninflammatory and inflammatory and UVRF assessment using Visiopor PP34 camera were done to all participants in 5 divided facial areas (forehead, nose, right and left cheeks, and chin). Clinical assessment for each patient was done by 3 dermatologists. Determination of correlation between UVRF with acne lesion counts was done using Pearson test and with acne severity using Spearman test. Results. From 45 participants, majority had moderate acne (64.4%), followed by severe (24.5%) and mild acne (11.1%). Mean number of UVRF spots was 39.98 ± 11.45 and percentage area covered with UVRF was 4.39 ± 1.72. There was no correlation found between acne lesion counts, including noninflammatory and inflammatory with the number and percentage area covered with UVRF spots. Severity grade of acne vulgaris was found to be uncorrelated with the number of UVRF spots (r = 0.27, p=0.073) and percentage area covered with UVRF spots (r = 0.173, p=0.256). Conclusion. The severity of acne vulgaris has no correlation with spot counts and percentage area covered with UVRF. Digital fluorescence might be helpful in investigating further of the interrelated pathogenesis factors of acne.